Interdisciplinary advances in adaptive and intelligent assistant systems concepts, techniques, applications, and use - Kreuzberger, Gunther; Lunzer, Aran; Kaschek, Roland (Premier reference source, 2011)
"This book discusses how collaboration between humans and intelligent systems can potentially improve access to and processing of complex information, contributing to the synthesis, storage and integration of knowledge" - Provided by publisher